(untitled) (Cadernos de Sociomuseologia, 2019)
This research has its organization based in scientific investigation and acts approaching the areas of Museology and Public Policies. The Brazilian cultural area has a difficult and complex path in the way to ensure the culture as citizen rights. The construction of a public policies to museums in Brazil is not different from others cultural areas, they all face for a long time a lack of planning and interest, politic neglect and the misunderstanding of culture as a factor of social development. In 2003, with a new minister of culture Gilberto Gil, the country started to think in a project to culture. At the museums field this project took shape with the National Policy for Museums that has its origins in the museology department movement which claimed for changes to the area and for the museums. By introducing the Brazilian System of Museums, the public policy program established a relationship from the net, the connections with the objective of participatory construction, collaborative and mainly with respect to diversity and promoting social inclusion. Based on reflections about politics, public policy and data from another country experiences, this thesis analyzes the foundation process of National Policy for Museums and the Brazilian Museum System performance and the consequences in museology practice and in established social relationships. Key words: Museology, Public Policies, Nets and Systems, National Policy of Museums, Brazilian System of Museums.